Section 4. The Diving Incident Reporting System (DIMS). - Buzzacott, Peter; Bennett, Caslyn; Denoble, Petar; Gunderson, Jim (Divers Alert Network, 2020)
The format of Edition 2019 is similar to that of previous editions. In Section One, we present 2017 fatality data. At the beginning of this section are summary statistics for fatalities in the U.S. and Canada followed by a series of case studies that offer further insight into causes.